Fundamentals of Human Geography - Cheung, Wing (Open textbook library., 2023)
Fundamentals of Human Geography is a college-level digital textbook aimed at introducing undergraduate students to the field of human and cultural geography. This digital textbook was initially conceived as an interactive supplemental guide for an open-source textbook on Human Geography (Introduction to Human Geography ). However, as more materials were added to this digital textbook, it slowly evolved into a standalone textbook on Human Geography which can be used by itself or as a supplemental guide. Be sure to explore all of the interactive content in each chapter and read the captions carefully, as a number of critical concepts are introduced in the interactive content. Be sure to also review the FAQ section for answers to commonly asked questions about technical aspects of this textbook.